2015
DOI: 10.1016/j.geomorph.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Flow deflection over a foredune

Abstract: Flow deflection of surface winds is common across coastal foredunes and blowouts. Incident winds approaching obliquely to the dune toe and crestline tend to be deflected towards a more crest-normal orientation across the stoss slope of the foredune. This paper examinesfield measurements for obliquely incident winds, and compares them to computational fluid dynamics (CFD) modelling of flow deflection in 10° increments from onshore (0°) to alongshore (90°) wind approach angles. The mechanics of flow deflection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
83
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 46 publications
21
83
1
Order By: Relevance
“…A more complex model might allow for unequal deposition of sediment across the dune form, and hence varying slope angles, but the general outcome would be similar in terms of overall morphodynamic evolution of the dune form. In this regard, it should be noted that the model is not driven by wind but simply by sediment inputs, and therefore there is no feedback between the evolving form and wind acceleration or steering through time (Hesp et al ., ). The initial foredune height was set at 3 m, which is reasonable for an established foredune and allows for the depiction of the triangular form.…”
Section: Computer Model Of Foredune Evolutionmentioning
confidence: 99%
“…A more complex model might allow for unequal deposition of sediment across the dune form, and hence varying slope angles, but the general outcome would be similar in terms of overall morphodynamic evolution of the dune form. In this regard, it should be noted that the model is not driven by wind but simply by sediment inputs, and therefore there is no feedback between the evolving form and wind acceleration or steering through time (Hesp et al ., ). The initial foredune height was set at 3 m, which is reasonable for an established foredune and allows for the depiction of the triangular form.…”
Section: Computer Model Of Foredune Evolutionmentioning
confidence: 99%
“…In the past decade, a series of papers describing wind flow over coastal foredunes at Magilligan Strand (Northern Ireland) and the Greenwich Dunes (Prince Edward Island, Canada) have yielded A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 significant insight into flow steering and topographic forcing (e.g., Walker et al, 2006Walker et al, , 2009Jackson et al, 2011;Bauer et al, 2012;Delgado-Fernandez et al, 2013;Lynch et al, 2009;Hesp et al, 2009Hesp et al, , 2015. In particular, these field experiments demonstrated that offshore flow can be substantially modified in the lee of a large coastal foredune, to the extent that shore-parallel steering and eddy recirculation occurs on the beach (Lynch et al, 2008;Bauer et al, 2012) as recognized by Hesp (2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3) for the crest tower shows that the flow was oriented almost perfectly offshore (southerly) at the start of the measurement interval, veering slightly to the southwest to a maximum of about 35 o by 16:15. At the dune crest surface (St 10), wind direction varied from -15 o (south southeasterly) to +15 o (south southwesterly), essentially crest normal flow for the duration of the period, indicating a localized, topographically-forced steering effect that constrained the near-surface flow to a crest normal orientation (cf.,Hesp et al, 2015). Wind gusts forced small deviations from these mean directions with instantaneous excursions less than about +/-20 o .…”
mentioning
confidence: 95%
“…This is particularly the case within trough blowouts, which have narrow and topographically constrained 'Vand U-shaped' morphologies. McKenna Neuman et al, 1997;Walker, 1999;Hesp et al, 2015;Smyth and Hesp, 2015) and turbulent kinetic energy (Smyth et al, 2014), these measurements alone are not direct indicators or predictors of whether sediment is being eroded, transported or deposited, which, in turn, limits their value for understanding the evolutionary dynamics of the system. However, the precise measurement of flow dynamics and resulting patterns of topographic change have not yet been performed in detail.…”
Section: Introductionmentioning
confidence: 99%